Petri Nets and Matrix Graph Grammars: Reachability - de Lara, Juan; Velasco, Pedro (Electronic Communications of the EASST, 2007)
This paper attempts to contribute in two directions. First, concepts and results of our Matrix Graph Grammars approach [VL06b, VL06a] such as coherence and minimal initial digraph are applied to Petri nets, especially to reachability criteria and to the state equation. Second, the state equation and related Petri nets techniques for reachability are generalized to cover a wider class of graph grammars.